Musicological Study Of Famözi Göndra in Si’ulu Death Ceremony in Bawömataluo Nias South, North Sumatera - Noverman, Fajar; Emridawati, Emridawati; Hendri, Yon; Wijaksana, Bambang (Institut Seni Indonesia Padangpanjang, 2024)
This article is the result of research into the Si'ulu death ceremony in the village of Bawömataluo, South Nias, Sumatra, Indonesia which uses Nias customs using the traditional art of Famözi Göndra which has a melodic interweaving of percussion instruments. This traditional music research is a qualitative research with a descriptive analysis method to analyse the musical elements found in the community of Bawömataluo Village, South Nias. Data coded from various performances of Famözi Göndra, in the form of musical elements, were reduced, then presented descriptively. The elements of traditional Famözi Göndra music include instruments and performers. In addition to musical elements such as: Rhythm, Melody, Timbre, and Tempo can be enjoyed by the audience.